2013
DOI: 10.3390/toxins5040784
|View full text |Cite
|
Sign up to set email alerts
|

From the Gut to the Brain: Journey and Pathophysiological Effects of the Food-Associated Trichothecene Mycotoxin Deoxynivalenol

Abstract: Mycotoxins are fungal secondary metabolites contaminating food and causing toxicity to animals and humans. Among the various mycotoxins found in crops used for food and feed production, the trichothecene toxin deoxynivalenol (DON or vomitoxin) is one of the most prevalent and hazardous. In addition to native toxins, food also contains a large amount of plant and fungal derivatives of DON, including acetyl-DON (3 and 15ADON), glucoside-DON (D3G), and potentially animal derivatives such as glucuronide metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
298
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(306 citation statements)
references
References 166 publications
(344 reference statements)
7
298
0
1
Order By: Relevance
“…Deoxynivalenol (DON) is the most common mycotoxin among the type B group of trichothecenes found at high concentration in cereals and mainly produced by F. graminearum and F. culmorum (Terzi et al 2007;Häller et al 2008;Miller 2008;Edwards 2009). The main features of DON on animals are constituted by an emetic effect (DON or "vomitoxin") and immunosuppressive effects also representing a risk for human health (SCF 2002;He et al 2010;Pestka and Smolinski 2005;Maresca 2013). T2 and HT2 toxins belong to the type A group of trichothecenes known as the most toxic members of this group of mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…Deoxynivalenol (DON) is the most common mycotoxin among the type B group of trichothecenes found at high concentration in cereals and mainly produced by F. graminearum and F. culmorum (Terzi et al 2007;Häller et al 2008;Miller 2008;Edwards 2009). The main features of DON on animals are constituted by an emetic effect (DON or "vomitoxin") and immunosuppressive effects also representing a risk for human health (SCF 2002;He et al 2010;Pestka and Smolinski 2005;Maresca 2013). T2 and HT2 toxins belong to the type A group of trichothecenes known as the most toxic members of this group of mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…The mean concentration of DON achieved 368.4 µg kg -1 . Next to DON, there are other masked forms of DON, deoxynivalenol-3-glucoside (D3G) or 3(15)-acetyldeoxynivalenol (3(15)-ADON), but changes among these forms are still insufficiently known (Maresca, 2013). Pazderu et al (2016) suggested high importance of evaluating not only DON, but all DON forms simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Ponadto w dostępnym piśmien-nictwie brak jest informacji na temat wpływu ZEN czy DON na populacje limfocytów krwi krezkowej. Uwzględniając fakt największego wchłaniania mikotoksyn fuzaryjnych na obszarze jelita cienkiego (15) należy się spodziewać, że we krwi naczyń krezkowych można będzie uzyskać największą koncentrację omawianych związków. Ponadto należy zwrócić uwagę, iż we wspomnianych naczyniach płynie krew, która dopiero zostanie dostarczona do wątroby, czyli centralnego narządu metabolicznego, który odpowiada za procesy detoksykacji.…”
Section: Praca Oryginalnaunclassified